The Development of the Russian Legal System after the “Accession” of the Republic of Crimea to the Russian Federation - Cwicinskaja, Natalia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
On March 18 2014, the Republic of Crimea became a federal subject of the Russian Federation and the Ukrainian legal system was changed to the Russian system. The transition period was set to end on January 1 2015. This transition period was characterized by the fact that the law was created on a day-to-day basis, and as the residents of Crimea were unfamiliar with Russian law they found themselves in a legal vacuum. Laws were adopted in an urgent manner to ensure that the unification was as smooth as possible. In practice it became apparent that the allocated time was not sufficient, and the transition period was extended in some areas. The Article presents a review of the accession procedure and the legal regulations established in the Republic of Crimea during the transition period, and identifies some issues which have arisen.